Screening and eradication of Helicobacter pylori to prevent gastric cancer in indigenous Taiwanese communities: a population-based study and development of an index-case method. (July 2022) - Lei, Wei-Yi; Lee, Jian-Yu; Chen, Chie-Lin; Bair, Ming-Jong; Wu, Jeng-Yih; Wu, Deng-Chyang; Tien, Hui-Wen; Lin, Li-Ju; Hsuttt, Tsui-Hsia; Lee, Yi-Chia
Abstract: Background: Gastric cancer is one of the leading causes of cancer death, particularly in Asia and South America. Screening and eradication of Helicobacter pylori is recognised as an advantageous solution to reduce the disparities in the incidence of this cancer. However, the deployment of such policies is not yet sufficiently advanced in high-incidence areas. Our study aimed to show the acceptability and feasibility of an index-case method to implement a screening and eradication policy in high-risk populations living in Taiwanese indigenous communities. Methods: We did a population-based study with residents aged 20–60 years from 454 tribes across 40 indigenous townships. H pylori infection was documented via the 13 C-urea breath test (Hwang's Pharmaceutical, Yunlin, Taiwan). When a participant tested positive for H pylori infection (constituting an index case), family members were invited to attend the screening service. H pylori carriers were referred for a four-drug antibiotic treatment course (lansoprazole 30 mg plus amoxicillin 1 g for the first 7 days, followed by lansoprazole 30 mg, clarithromycin 500 mg, and metronidazole 500 mg for another 7 days; all drugs given orally twice daily). Those who did not respond to the initial course of antibiotics were retreated with a 10-day treatment that consisted of a bismuth-based four-drug treatment (lansoprazole 30 mg twice daily, bismuth(III) oxide 120 mg four times a day, amoxicillin 500 mg four times a day, and tetracycline 500 mg four times a day; all drugs given orally) or a levofloxacin-based three-drug treatment (lansoprazole 30 mg twice daily, amoxicillin 1 g twice daily, and levofloxacin 500 mg once daily; all drugs given orally). Primary outcomes were the acceptability and feasibility of this screening method, which were evaluated according to the participation rate, test positivity rate, referral-to-treatment rate, and the eradication rate. Analyses were done in the intention-to-treat and per-protocol analyses. The adverse effect during treatment and the reinfection rate two years after treatment were also evaluated. This study is registered with ClinicalTrials.gov, NCT03900910, and is enrolling. Findings: Participants were enrolled between Sept 24, 2018, and Dec 31, 2021. The participation rate was 15 057 (80·0%) of 18 821 invitees. 9600 (63·8%) of 15 057 participants were women and 5457 (36·2%) were men, with a median age of 44·5 years (IQR 35·7–53·0). The test positivity rate was 6643 (44·1%) of 15 057 (95% CI 43·3–44·9%). 8852 (58·8%) participants were indigenous Taiwanese and had a positivity rate of 5055 (57·1%). 6205 (41·2%) of 15 057 were non-indigenous and had a positivity rate of 1588 (25·6%). Family members of participants who tested positive (positive index cases) had a 1·98 times (95% CI 1·03–3·80) higher prevalence of H pylori infection than the family members of those who tested negative (negative index cases), adjusted for the age, sex, and the social habits. 5493 (82·6%) of 6643 participants who tested positive received antibiotic treatments. The reinfection rate was estimated at 1·79 (95% CI 1·04–3·08) per 100 person-years. According to the intention-to-treat and per-protocol analyses, the eradication rates were 78·5% (95% CI 76·3–80·3%) and 79·5% (77·2–81·7%), respectively, after one course of antibiotic treatment, and 91·7% (CI 89·1–94·3%) and 92·1% (89·2–95·0%), respectively, after two courses of antibiotic treatment. The rate of adverse effects leading to treatment discontinuation was low (66 [1·2%] of 5493 patients [95% CI 0·9–1·5%]). Interpretation: Mass screening and eradication of H pylori is acceptable and feasible for populations with a high prevalence of H pylori infection and a high incidence rate of gastric cancer, such as people living in the indigenous communities in Taiwan. Expanded programmes based on the index-case method and family outreach can accelerate progress toward the elimination of the health disparities around H pylori -related diseases. Funding: Health Promotion Administration, Ministry of Health and Welfare, Taiwan (grant number A1101008).